Reasons Of Nurses In Pursuing Professional Advancement - Nagtalon, Federico V.; Ramos, Precylou C. (Journal of International Scholars Conference - ALLIED HEALTH, 2016)
This study was conducted to determine why nurses in a government hospital in Laoag City, Philippines pursue professional advancement. Specifically, it attempted to identify the respondents’ socio-demographic profile and their attendance to graduate school studies, seminars, symposia, trainings and workshops using the descriptive research design. The study found that most of the respondents are young adults, females, Roman Catholic and with an average income. Each nurse handles an average of 31-40 patients for eight hours a day. Most of the respondents have not attended graduate school classes; are classified as Nurse I and attended at most five seminars, symposia, trainings and workshops at the local level; only a few have attended symposia, trainings and workshops at the regional and national levels. Most of the respondents agreed that their occupational reason in attending professional advancement is for professional growth and to be updated on trends in nursing. Personal reason includes for self-development and to learn new things and ideas. As to support system, most of them were supported by their immediate superiors and that they shoulder their own expenses in attending professional advancement.